Cohort Profile: The Shanghai Sleep Birth Cohort Study. Issue 2 (18th December 2020) - Lin, Jianfei; Sun, Wanqi; Song, Yuanjin; Dong, Shumei; Lin, Qingmin; Deng, Yujiao; Meng, Min; Zhu, Qi; Jiang, Yanrui; Wang, Guanghai; Tong, Shilu; Liu, Shijian; et al.
Abstract: Background: Sleep disturbances in women occur frequently throughout pregnancy. Previous studies have demonstrated that the increasing incidence of physiological and psychological illness is concurrent with increasing sleep deprivation and poor sleep quality in adults and children. Objectives: The Shanghai Sleep Birth Cohort Study (SSBCS) was established to examine the effect of sleep disturbances during the third trimester on emotional regulation of mothers; to assess the effect of maternal sleep during pregnancy on the growth and development of children; and to explore the influence of children's sleep characteristics on physical and social‐emotional development. Population: The study was conducted in the Renji Hospital in Pudong New District, Shanghai from May 2012 to July 2013. Women and their newborns who met the inclusion criteria and agreed to participate in this study were recruited to the SSBCS. Methods: The follow‐up visits for children were conducted at the age of 42 days, 3, 6, 9, 12, 18, and 24 months, and 3, 4, and 6 years. Data on demographic factors, physical examination, sleep assessment, developmental and psychiatric assessment, diet records, and biological samples were collected throughout the study. Preliminary results: A total of 277 pregnant women were recruited to the study; the response rate was 64.3%. 37.9% of the pregnant women had poor sleep quality and 12.0% suffered from depression. Infant sleep patterns changed during the first year of life, but most sleep characteristics showed little variation from 6 to 12 months. Conclusions: The SSBCS is an on‐going prospective cohort study with follow‐up to 6 years. The detailed data on demographic factors, sleep assessment, physical examinations, neurodevelopmental and psychiatric assessment, diet records, and biological samples make this research platform an important resource for examining the potential effects of sleep characteristics on both maternal and child health.